Proposed new interior design scheme of Indie Music Centre for Yamaha Music (Malaysia) Sdn. Bhd. at Jalan Metro Pudu 1, Fraser Business Park, Off Jalan Yew 55200 Kuala Lumpur / Muahammad Anas Othman - Othman, Muahammad Anas (Faculty of Architecture, Planning and Surveying, 2012)
This project related with the “Intipati Rancangan Malaysia ke-10 (2011-2015)” that provide opportunities to the private sector cooperate with the Government. In addition, this project is also supported by the Government under the Belia 1 Malaysia program. Next, the project is the request itself from YAMAHA MUSIC (Malaysia) Sdn. Bhd. to open a music center preferred by the youth of today and the concept is simple. This is because, YAMAHA MUSIC (Malaysia) already have music lessons at more luxurious concept is only suitable for high-income groups. (Results from the interviews made). The Indie Music Centre is serves as an opportunity / platform to those who love art and film music indie (independent), which provides an easy way for them (youth) to share experiences, skills, and abilities in the arts of music and film indie (independent) under the same roof. Finally, the center also serves to help those who have the talent in the music art and film art indie (independent) to deliver their ambitions with the orderly and systematic manner. The aim for this project is to create the first independent music centre for YAMAHA MUSIC (Malaysia) at Malaysia.The objective for this project is to create welcoming sense to new indie music centre for Yamaha Music (Malaysia) Sdn. Bhd. Secondly, To research more depth about the system of acoustic(sound system) to be applied in the interior while the music operate in the building, especially when the musical performance going. Next, to explore and study about music centre that involves music and film arts for youth. Futhermore, to designs and maximize the use of a space for a number of visitors who crowd in a certain time and divided space according to a variety of activities in one building. Moreover, to create a comfortable space centre and customer friendly to tourist. The competitive environment in centre and music industry is expected to get more intense. There are lot of music centre have been set up in every states in Malaysia and more are still to come. To succeed in this business, the owner will have to rethink their existing work practices and business strategies to see if more efficiencies and competitive advantage can be secured by doing things differently. This proposal is to open new concept centre of Yamaha Music (Malaysia) at Jalan Metro Pudu 1, Fraser Business Park, Off Jalan Yew 55200 Kuala Lumpur. The main objective is to introduce a ‘Rhythm’ concept and ‘Modern’ design to follow the client corporate image and identity. This centre is different from other music centre. It will be a hot spot for the indie music fans. The idea to undertake this project was given due attention after taking into consideration the current and design issues, and to solve the problems encountered by the music centre efficiently. Therefore, a plan was proposed to prepare new design and approach that may interest and fulfill the aspiration of the client, workers and customer. Design scheme concept should be taken into account as profoundest study. From the research and observation conducted, all data and details gathered was used as a guideline in the design process. Finally, reorganized space requipments by function and capacity visitors at one specific time. The concept that has been applied in this project is the Rhythm that is movement of the pattern. (Kementerian Kerajaan Malaysia, 2011)